(untitled) - Phillips, Robert Brooks (Cambridge UK, 2001)
A central tenet of materials analysis is the structure-property paradigm, which proposes a direct connection between the geometric structures within a material and its properties. The increasing power of high-speed computation has had a major impact on theoretical materials science and has permitted the systematic examination of this connection between structure and properties. In this textbook.
Keywords: Crystal lattices,Crystals,Tinh thể,Crystals,Tinh thể; Defects,Khuyết tật